Cardiovascular disease and beta-cell function at diagnosis of serologically defined adult-onset type 1 and type 2 diabetes in two Swedish cohorts 15 years apart - Ritsinger, Viveca; Gunnarsson, Rebecka; Melin, Eva; Hillman, Magnus ; 0000-0001-6749-2829; Stogianni, Anna; Holmberg, Sara; Johansson, Karin; Nilsson Neumark, Ann-Sofie; Krol, Herbert; Rööst, Mattias; Landin-Olsson, Mona; Neumark, Thomas; et al. (BMJ Open, 2025)
OBJECTIVES: To describe the prevalence of cardiovascular disease (CVD) at the time of diagnosis of adult-onset type 1 (T1D) and type 2 (T2D) diabetes, in a recent cohort and compare to a previous cohort from the same region. Further, to explore factors influencing the prevalence of pre-existing CVD, including age, sex, body mass index (BMI) and C-peptide; in the later cohort also heart failure, hyperlipidaemia, tobacco use and physical activity. DESIGN: Two prospective cross-sectional cohort studies compared. SETTING: All primary health care centres and hospitals in Kalmar and Kronoberg counties in Southeastern Sweden. PARTICIPANTS: Adults with newly diagnosed T1D or T2D (classified by combination of islet antibodies and C-peptide) in 1998-2001 and 2016-2017. PRIMARY AND SECONDARY OUTCOME MEASURES: Prevalence of hypertension and CVD at diagnosis of diabetes, and associations with beta-cell function, in two cohorts collected 15 years apart. Further, to explore factors influencing the prevalence of hypertension and CVD, and level of C-peptide. RESULTS: In patients with newly diagnosed T2D, mean age-at-onset had decreased (66±14.1 years vs 63±12.6, p≤0.001) and mean BMI had increased (29.0±5.4 vs 31.4±5.8 kg/m 2, p≤0.001). Prevalence of pre-existing myocardial infarction had decreased in both T1D (18% vs 7%, p=0.03) and T2D (25% vs 11%, p≤0.001). Pre-existing hypertension had increased in both T1D (23% vs 40%, p=0.01) and T2D (44% vs 61%, p≤0.001). C-peptide level was lower and was associated with several cardiovascular conditions in newly diagnosed T2D in 2016-2017 (p=0.048 p≤0.001). CONCLUSIONS: Patients with newly diagnosed T2D were younger, with higher BMI, compared with 15 years earlier, a challenge for diabetes care. Prevalence of pre-existing myocardial infarction had decreased notably, in line with, but still less than in the general population; while pre-existing hypertension had increased, in both diabetes types. C-peptide was associated with several cardiovascular conditions in newly diagnosed T2D in the recent cohort, which warrants further investigation.
© Author(s) (or their employer(s)) 2025. Re-use permitted under CC BY. Published by BMJ Group.
Keywords: Humans; Sweden/epidemiology; Male; Female; Middle Aged; Cross-Sectional Studies; Diabetes Mellitus, Type 2/epidemiology; Cardiovascular Diseases/epidemiology; Insulin-Secreting Cells/physiology; Prospective Studies; Aged; Prevalence; Diabetes Mellitus, Type 1/epidemiology; Body Mass Index; C-Peptide/blood; Age of Onset; Hypertension/epidemiology; Adult; Risk Factors